Go backward to Quantifier Consequences (Continued)Go up to TopGo forward to Example |

**De Morgan Laws**-
~ **forall**`x`:`A`**exists**`x`: ~`A`**exists**`x`: ~`A`~ **forall**`x`:`A`~ **exists**`x`:`A`**forall**`x`: ~`A`**forall**`x`: ~`A`~ **exists**`x`:`A` **Such Quantifier**-
**exists**`x`:`A``A`[`x`<-**such**`x`:`A`]( **forall**`y`_0,`y`_1: (`A`[`x`<-`y`_0] /\`A`[`x`<-`y`_1]) =>`y`_0 =`y`_1)( **forall**`x`:`A`=>`x`=**such**`x`:`A`)

Author: Wolfgang Schreiner

Last Modification: November 30, 1999